The Role of G-proteins and G-protein Regulating Proteins in Depressive Disorders - Senese, Nicolas B.; Rasenick, Mark M.; Traynor, John R. (Frontiers in Pharmacology, 2018)
Progress towards new antidepressant therapies has been relatively slow over the past few decades, with the result that individuals suffering from depression often struggle to find an effective treatment - a process often requiring months. Furthermore, the neural factors that contribute to depression remain poorly understood, and there are many open questions regarding the mechanism of action of existing antidepressants. A better understanding of the molecular processes that underlie depression and contribute to antidepressant efficacy is therefore badly needed. In this review we highlight research investigating the role of G-proteins and the regulators of G-protein signaling (RGS) proteins, two protein families that are intimately involved in both the genesis of depressive states and the action of antidepressant drugs. Many antidepressants are known to indirectly affect the function of these proteins. Conversely, dysfunction of the G-protein and RGS systems can affect antidepressant efficacy. However, a great deal remains unknown about how these proteins interact with antidepressants. Findings pertinent to each individual G-protein and RGS protein are summarized from in vitro, in vivo, and clinical studies.